Homes around the world - Kalman, Bobbie, 1947- (New York : Crabtree Pub. Co., 1994)
Looks at various kinds of dwellings, including arctic homes, homes on stilts, homes on boats, and desert homes.
Includes glossary and index.
Teacher Librarian
3.9
K-3
Keywords: Dwellings -- Cross-cultural studies -- Juvenile literature; Dwellings; Houses